Consumer interest and willingness to pay for in-bulk products with reusable packaging options - Patreau, Valérie; Bernard, Sophie; Leroux, Justin; Bellemare, Marie; Morissette, Joliann (Frontiers in Sustainability, 2023)
Consumers are looking for solutions to reduce waste at source, especially plastic waste from single-use packaging. Simply recycling packaging will not be enough and reduction at the source must be emphasized as part of a sustainable circular economy. Selling products in bulk using reusable containers is one of the emerging paths of the zero-waste movement. To achieve this, it is necessary to change consumption patterns and behaviors.Our goal is to better understand how source reduction of plastic packaging can be an asset in a zero-waste objective. Using a contingent valuation method, we conducted a large pan-Canadian survey on the purchasing preferences of 2002 Canadian households to analyze the willingness to pay (WTP) for different food and household products. Results indicate that most consumers do not appear to be willing to pay more for bulk products with reusable packaging even if they are interested in buying more bulk products. Different sociodemographic and attitudinal parameters, such as age, gender, sense of convenience, and pro-environmental behaviors, influence willingness to buy and pay. The originality of this work is to provide an economic perspective on the reduction of single-use containers and changes in consumption practices in the context of the zero-waste movement and the circular economy.